(untitled) (Journal of Hama University, 2025)
The research aimed to identify the degree of application of digital leadership among principals of schools in the first cycle of basic education from the point of view of female teachers in the city of Tartous. The research sample consisted of (367) female teachers of the first cycle of basic education in the city of Tartous, according to the research variables (academic qualification). , teaching experience), and to achieve the goal of the research, reliance was placed on the descriptive analytical approach, and a questionnaire consisting of (25) items was used, which included five dimensions (planning, empowerment, system design, professional development, digital citizenship) prepared by the researcher, after it was Verifying its validity and reliability, the results were as follows: - The degree of application of digital leadership among school principals in the first cycle of basic education from the point of view of female teachers in the city of Tartous is average, with an arithmetic mean (2.92) and a standard deviation (0.529). - There are no statistically significant differences at the significance level (0.05) between the average scores of teachers’ answers to the digital leadership questionnaire according to the academic qualification variable. - There are statistically significant differences between the average scores of teachers’ answers to the digital leadership questionnaire according to the variable of teaching experience, for the benefit of 10 years or more. In light of the results obtained, the current research suggested the need to design training programs dedicated to developing the capabilities of school principals in the field of digital leadership, promoting a culture of continuous learning and professional modernization among school principals and teachers, through organizing educational workshops and seminars on the latest educational technologies.